Penerapan Teori Multiple Intelligences pada Desain Interior Study Lounge di Surabaya - Jocelyn Salim; Mariana Wibowo (Intra, 2019)
Today's teenagers lifestyles often spend their time hanging out or doing assignments at cafes, especially in the city of Surabaya. From the results of a survey conducted by the author, 36,92% said learning / working in a café was ineffective, while 12,3% said it was dependent on the facilities and design provided. That is, half of the sample felt that learning / working in a café had several problems. From these problems, came the idea to design a place for senior high school students and college students devoted to study (Study Lounge) and addition of facilities for work (co-working space). Considering nowadays, not a few students that work while studying, at the same time it can be used for workers to be able to establish relationships with students. This design innovation applies multiple intelligences with the awareness that everyone has different styles of working / learning, so it is hoped that with the study lounge and co-working space it can accommodate all people to learn and work effectively. Because everyone has different learning styles and work, so they cannot be evenly distributed. The design method used is the stage of design thinking process according to Stanford D. School, that is empathize, define, ideate, prototype and test. The result of the design is a space that accommodates the needs of senior high school and college students in learning and doing assignments. This design is also an alternative solution for new learning places in Surabaya by adopting the concept of “Unity in Diversity” which accommodates the many needs of each different multiple intelligences.